Elabela levels in patients with type 2 diabetes: can it be a marker for diabetic nephropathy? - Onalan, Erhan; Dogan, Yusuf; Onalan, Ebru; Gozel, Nevzat; Buran, Ilay; Donder, Emir (Makerere Univ, Fac Med, 2020)
Backround: Elabela (ELA) is a hormone that is secreted at high levels in the kidneys of a healthy adult. This study aims to investigate whether serum ELA levels of patients with Type 2 Diabetes vary with the severity of renal damage. Methods: Our study included 50 healthy control subjects and 100 diabetic patients, who were categorized into groups based on urine albumin/creatinine ratios (ACR). Patients included in the study were assigned to four groups: Group 1 (healthy control), Group 2 (ACR<29mg/g), Group 3 (ACR=30-299 mg/g), and Group 4 (ACR>300 mg/g normal or high serum creatinine). Physical examination findings, demographic characteristics of the study group were recorded, and serum ELA levels and other laboratory parameters were assessed using appropriate methods. Results: The results of the study indicated that ELA levels determined in healthy individuals gradually decreased through stages of normal albuminuria, microalbuminuria, and macroalbuminuria. Moreover, ELA had a significant negative correlation with LDL-C (r=-0.201, p=0.014), glucose (r=-0.437, P<0.001), retinopathy (r=-0.222, P=0.006), serum BUN (r=0.161, P=0.049), and a positive correlation with eGFR (r=0.250, P=0.002). Conclusions: The fact that ELA levels are higher in healthy individuals compared to diabetic patients without microalbuminuria, and higher in diabetic patients without microalbuminuria compared to patients with advanced albuminuria and kidney damage, suggests that the ELA level can be an important clinical prognostic variable and even a promising agent for the treatment of diabetic nephropathy patients.
Keywords: Elabela; diabetes; diabetic kidney disease; albuminuria